Adsorption of metals by geomedia II : variables, mechanisms, and model applications - Barnett, Mark O.; Kent, Douglas B. (Developments in earth & environmental sciences, 2008)
Adsorption of Metals by Geomedia II serves as a needed resource for this topic which has received much attention during the past 25 years. The book provides an in-depth review of the field, followed by numerous chapters that document the current status of adsorption research for a variety of metals by geomedia ranging from individual minerals to sediments and soils. Adsorption mechanisms are detailed and precipitation is presented as a distinct sorption process. Virtually all factors affecting the extent of metal adsorption are examined, including the effects of selected anions, competition among metals, pH, metal concentration, loading, variable metal adsorption capacity, ionic strength, hydrogen exchange and stoichiometry, and solids concentration. A variety of adsorption models are briefly presented and some are used to extend laboratory studies to field sites. This is a compilation of 25 peer reviewed papers from among the 60+ platform and poster presentations of the symposium "Adsorption of Metals to Geomedia II" at the American Chemical Society (ACS) Meeting, March 27-29, 2006 in Atlanta, Georgia, USA. This symposium is a follow-up to the original held in 1996. * Learn the tools and techniques from leading academics and industry experts * One stop practical resource and guide for those in the field * Keep informed and up to date on all the latest advancements in technology